Human rights violations in medicine: a-to-z action guide by Dr. Pamela Wible - Erin Nissen Castelloe (Qualitative Research in Medicine & Healthcare)
To organize work in such a manner that it becomes meaningless, boring, stultifying, or nerve-racking for the worker would be little short of criminal; it would indicate a greater concern with goods than with people, an evil lack of compassion and a soul-destroying degree of attachment to the most primitive side of this worldly existence.